How Good Does This Sound? Examining Listeners’ Second Language Proficiency and Their Perception of Category Goodness in Their Native Language - Charlie Nagle; Melissa M. Baese-Berk; Carissa Diantoro; Haeun Kim (Languages, 2023)
Language learners often transfer the sounds and prosody of their native language into their second language, but this influence can also flow in the opposite direction, with the second language influencing the first. Among other variables, language proficiency is known to affect the degree and directionality of cross-linguistic influence. However, little is known about how second language learning affects listeners’ perception of their native language. To begin addressing this gap, we examined the relationship between learners’ second language proficiency and their category goodness ratings in their native language. Thirty-nine English-speaking learners of Spanish listened to English words that began with voiced and voiceless stop consonants and were asked to rate how well the word represented the intended word on a 5-point scale. To create a voicing continuum, we manipulated the voice onset time of the word-initial stop in each target item from 125 ms of prevoicing to 100 ms of aspiration, in 25 ms steps. Proficiency did not affect the perception of voiced targets, but both proficiency and L2 stop production affected the perception of voiceless targets.